(untitled) (Journal of Philosophy, Culture and Political Science, 2018)
The development of regionalism processes is the most important characteristic of the modern world economy. The processes of international economic integration significantly intensified in the second half of the twentieth century in various regions of the globe, in particular in the post-Soviet space. The sharp increase in inter-firm and inter-state competition, new spheres of competition and tougher competition in traditional markets necessitates cooperation of both financial and production efforts of geographically connected countries, allows strengthening its positions in the globalizing economy. Over the past 25 years, regionalization in the post-Soviet space has ensured the unity of goals and means governing the progressive development of the CIS (Commonwealth of Independent States) countries based on trade and production ties and proves the need for further development of the process at a high pace. Key words: regionalism, integration, globalization, Commonwealth of Independent States (CIS), Eurasian Economic Union (EAEU), Eurasian Customs Union (EACU).